Jurisdiction for the modification of a decision on access rights. Purpose to the CJEU (Ninth Chamber) Judgement of 27 April 2023, Case C 372/22 - Carrillo Pozo, Luis F. (CUADERNOS DE DERECHO TRANSNACIONAL, 2024)
The art. 8 of regulation 2019/1111 (equivalent to art. 9 of 2201/2003) confers jurisdiction to modify the access rights regime to a minor to the same court that ruled on this matter, when the conditions expressly provided for therein are met. Underlying these standards are reasons of effectiveness, fundamentally. But there are situations in which there is a lack of sufficient minimum proximity to justify this continuing jurisdiction. In this context, the transfer of the dispute to another court can become an appropriate instrument to safeguard the essential principles and objectives of the system.